The selective orexin receptor 1 antagonist ACT-335827 in a rat model of diet-induced obesity associated with metabolic syndrome - Steiner, Michel A.; Sciarretta, Carla; Pasquali, Anne; Jenck, Francois (Frontiers in Pharmacology, 2013)
The orexin system regulates feeding, nutrient metabolism and energy homeostasis. Acute pharmacological blockade of orexin receptor 1 (OXR-1) in rodents induces satiety and reduces normal and palatable food intake. Genetic OXR-1 deletion in mice improves hyperglycemia under high-fat (HF) diet conditions. Here we investigated the effects of chronic treatment with the novel selective OXR-1 antagonist ACT-335827 in a rat model of diet-induced obesity (DIO) associated with metabolic syndrome (MetS). Rats were fed either standard chow (SC) or a cafeteria (CAF) diet comprised of intermittent human snacks and a constant free choice between a HF/sweet (HF/S) diet and SC for 13 weeks. Thereafter the SC group was treated with vehicle (for 4 weeks) and the CAF group was divided into a vehicle and an ACT-335827 treatment group. Energy and water intake, food preference, and indicators of MetS (abdominal obesity, glucose homeostasis, plasma lipids, and blood pressure) were monitored. Hippocampus-dependent memory, which can be impaired by DIO, was assessed. CAF diet fed rats treated with ACT-335827 consumed less of the HF/S diet and more of the SC, but did not change their snack or total kcal intake compared to vehicle-treated rats. ACT-335827 increased water intake and the high-density lipoprotein associated cholesterol proportion of total circulating cholesterol. ACT-335827 slightly increased body weight gain (4% versus controls) and feed efficiency in the absence of hyperphagia. These effects were not associated with significant changes in the elevated fasting glucose and triglyceride (TG) plasma levels, glucose intolerance, elevated blood pressure, and adiposity due to CAF diet consumption. Neither CAF diet consumption alone nor ACT-335827 affected memory. In conclusion, the main metabolic characteristics associated with DIO and MetS in rats remained unaffected by chronic ACT-335827 treatment, suggesting that pharmacological OXR-1 blockade has minimal impact in this model.